Mapping the playing field—a novel web-based strategy to identify non-governmental actors in global surgery. (27th April 2015) - Ng-Kamstra, Joshua S; Arya, Sumedha; Chung, Timothy E; Weston, Brad; Frankfurter, Claudia; Gutnik, Lily A; Kreutzer, Tino; Riesel, Johanna N; Meara, John G
Abstract: Background: In the face of staggering global unmet need for surgical care, non-governmental organisations (NGOs) play a substantial part in the surgical workforce, providing surgical care for those who are without it. The number of NGOs providing surgical care in low-income and middle-income countries (LMICs) is unknown. This information is needed to determine the scope of such care, its contributions to global surgical case volume, to improve collaboration in an effort to maximise efficiency, and to inform national surgical workforce planning. We aimed to create a comprehensive, publicly available catalogue of NGOs providing surgery in LMICs. Methods: We used the United Nations Rule Of Law definition to define NGOs. We included low-income, lower-middle- income, and upper-middle-income countries as defined by World Bank lending groups. Delivery of surgical care by an NGO was defined as the therapeutic manipulation of tissues taking place within an operating room, and was distinguished from the financial or logistical support of such care. We screened an online humanitarian clearing house (ReliefWeb), a large public NGO database (Idealist.org ), two surgical volunteerism databases (Operation Giving Back and the Society for Pediatric Anesthesia), and the US State Department Private Volunteer Organizations database, did a review of the literature, and used a social media outlet (Twitter) to identify organisations meeting criteria for inclusion. A complementary analysis additionally provided a list of organisations delivering exclusively surgical care from a search of the OmniMed database, the Foundation Center Online Directory, UK Charity Commission, Australia Charity Commission, New Zealand Charity Commission, and the Canada Revenue Agency Charity Search. Findings: We identified 313 unique organisations, working in all 139 LMICs. Organisations often used more than one model of care and engaged in several surgical specialties. Both short-term surgical missions (206 organisations, 66%) and long-term partnerships (213, 68%) were common models, with 40 organisations (13%) engaging in humanitarian interventions in crisis settings. The most commonly represented specialty was general surgery (120, 38%), but subspecialty surgery such as ophthalmology (88, 28%) and cleft lip and palate surgery (70, 22%) were also frequently performed. Interpretation: To our knowledge, this is the most complete directory of NGOs undertaking surgery in resource-limited settings in existence. However, it is difficult to determine whether this review is exhaustive. Further work is needed to determine the total and relative contributions of these organisations to global surgical volume. This database will be made available for public use and should be maintained and updated to further coordinate global efforts and maximise impact. Funding: None.